2011
DOI: 10.1111/j.1460-9568.2011.07766.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism behind gamma band activity in the pedunculopontine nucleus

Abstract: The pedunculopontine nucleus (PPN), part of the reticular activating system, modulates waking and paradoxical sleep. During waking and paradoxical sleep, EEG responses are characterized by low amplitude, high frequency oscillatory activity in the beta/gamma band range (~20–80 Hz). We reported that gamma band activity may be intrinsically generated by the membrane electroresponsiveness of PPN neurons, and that the neuronal ensemble generates different patterns of gamma activity in response to specific transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
246
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(272 citation statements)
references
References 50 publications
25
246
1
Order By: Relevance
“…These findings revealed one of the main characteristics of PPN neuronal gamma-frequency oscillations, showing that the membrane potential at the soma had to be gradually depolarized up to approximately Ϫ20 mV (using 2-s current ramps) to activate high-threshold, voltage-dependent P/Q-type calcium channels, and to a lesser extent, N-type calcium channels, that mediate high-frequency oscillations. That is, we found that P/Q-type channels were essential for eliciting the oscillations, but N-type channels were only permissive (Kezunovic et al 2011). The membrane potential at the dendrites, where these calcium channels are located (Hyde et al 2013a,b), was closer to physiological levels.…”
Section: Whole Cell Patch-clamp Recordingsmentioning
confidence: 68%
See 4 more Smart Citations
“…These findings revealed one of the main characteristics of PPN neuronal gamma-frequency oscillations, showing that the membrane potential at the soma had to be gradually depolarized up to approximately Ϫ20 mV (using 2-s current ramps) to activate high-threshold, voltage-dependent P/Q-type calcium channels, and to a lesser extent, N-type calcium channels, that mediate high-frequency oscillations. That is, we found that P/Q-type channels were essential for eliciting the oscillations, but N-type channels were only permissive (Kezunovic et al 2011). The membrane potential at the dendrites, where these calcium channels are located (Hyde et al 2013a,b), was closer to physiological levels.…”
Section: Whole Cell Patch-clamp Recordingsmentioning
confidence: 68%
“…The role of gamma activity in the PPN was proposed to underlie the process of preconscious awareness : in other words, to participate in the essential mechanism that allows the uninterrupted flow of afferent sensory information necessary for the "stream of consciousness" (James 2007). We also discovered that gamma oscillations in the PPN and ILT are based on high-threshold, voltage-dependent N-and P/Q-type calcium channels (Kezunovic et al 2011. We localized P/Q-type calcium channel-mediated oscillations to the dendrites of PPN and Pf cells (Hyde et al 2013a,b).…”
mentioning
confidence: 97%
See 3 more Smart Citations